IMPLEMENTASI DATA MINING PENJUALAN KOSMETIK DENGAN ALGORITMA APRIORI - Ulkhairi, Meta; Hutabri, Ellbert (Computer Science and Industrial Engineering, 2020)
Along with the times, data mining has been applied in various fields, including business or commerce, education and telecommunications. The rapid development of technology makes more and more competitors in the business world. Like Yati Cosmetics Shop, which sells various cosmetic brands, which still uses manual methods to collect data. So it is difficult to know which products (goods) are often sold, so Yati Cosmetics stores find it difficult to find cosmetics that are no longer available. Know the types of cosmetics most sold and cosmetics stocks that are still available, as well as the benefits of data mining in the sales system. The data used previously is data that has passed the selection stage in advance by researchers, so that it is easier to find the results of data analysis of cosmetics sales transactions at the Yati Cosmetics store. With priori algorithm calculations, the most commonly purchased product results are consumers, namely mirabella powder, inez powder, maybellin powder, pixy lipstick, and make over lipstick with a minimum support value of 44% and a minimum trust value of 80% with the final rule obtained from 9 rules with 83%, 84% and 89% confidence. Keywords : Data Mining, Apriori algorithm, Tanagra